2022
DOI: 10.3892/ol.2022.13372
|View full text |Cite
|
Sign up to set email alerts
|

Origin recognition complex 1 regulates phospholipase Cδ1 to inhibit cell proliferation, migration and epithelial‑mesenchymal transition in lung adenocarcinoma

Abstract: As a common pulmonary malignant disease, lung adenocarcinoma exhibits high mortality and morbidity rate. Phospholipase Cδ1 (PLCD1), an enzyme involved in the homeostasis of energy metabolism, is downregulated in lung adenocarcinoma. According to GEPIA, origin recognition complex 1 (ORC1) is a highly expressed gene in lung adenocarcinoma and is negatively associated with PLCD1. To the best of our knowledge, the present study was the first to investigate the role of ORC1 in regulating PLCD1 in lung adenocarcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Recently, aberrations in ORC1L have been implicated in breast cancer [66], cervical cancer [67], as well as LUAD cancer progression [68]. Investigating the role of ORC1L more closely, we found that aberrations in ORC1L gene expression have been previously linked with LUAD tumor growth [68,69] through changes in immune cell infiltration [68]. Han et al, [68] postulated that ORC1L promotes LUAD tumor progression and aberration of immune infiltration by deregulating WNT signaling pathway.…”
Section: Plos Onementioning
confidence: 64%
“…Recently, aberrations in ORC1L have been implicated in breast cancer [66], cervical cancer [67], as well as LUAD cancer progression [68]. Investigating the role of ORC1L more closely, we found that aberrations in ORC1L gene expression have been previously linked with LUAD tumor growth [68,69] through changes in immune cell infiltration [68]. Han et al, [68] postulated that ORC1L promotes LUAD tumor progression and aberration of immune infiltration by deregulating WNT signaling pathway.…”
Section: Plos Onementioning
confidence: 64%
“…8 , Wilcoxon test, p.adj < 0.05, fold change > 2). Among them, the upregulated proteins such as Orc1 49 , TGFBI 50 , MSLN 51 , HtrA1 52 , 53 were reported to be associated with the migration and invasion of tumor cells. The expression levels of these proteins in the different clusters were quantified (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In A549 cells, PLCδ1 overexpression inhibits proliferation, cell invasion, migration, and epithelial–mesenchymal transition in LC cells. Moreover, in A549 cells, ORC1 binds to the PLCδ1 promoter, significantly reducing PLCδ1 expression, which may affect the progression of LC [ 60 ]. PLCδ1 acts as a tumor-suppressor gene in various tumors, and it is epigenetically silenced through hypermethylation in esophageal squamous cell carcinoma, breast cancer, gastric cancer, and chronic myeloid leukemia [ 32 ].…”
Section: Plc and Lung Cancermentioning
confidence: 99%